LIQUIDITY MANAGEMENT OF COMMERCIAL BANKS - Putintseva, Tetyana (Socio-economic relations in the digital society, 2020)
Imperfect liquidity management of a commercial bank can provoke a shortage / excess / imbalance of liquidity, which will worsen the general conditions of banking institutions, their financial stability, stability and ultimately undermine their financial security. Therefore, the task of the article is to analyze the existing theories of liquidity management of a commercial bank with the definition of their content and shortcomings, the essence of such management, the methods and tools used for this, as well as liquidity regimes. The importance of liquidity management of commercial banks is determined. Emphasis is placed on the need to identify in the course of the liquidity study of commercial banks the characteristics of liquid resources attracted by them, the liquidity of their assets, as well as finding the optimum in the management of such assets and liabilities. The sources of raising funds, which can be quickly realized if necessary, in the amount necessary to cover the demand for liquid funds, are described. The evolution of liquidity management theories is analyzed and critically evaluated, their content is specified and shortcomings are revealed. The essence of liquidity management of a commercial bank according to process and system approaches is considered. The liquidity regimes of commercial banks using its different models are given. The methods and author’s vision of liquidity management tools of commercial banks are presented, to which it is proposed to include: instruments of reservation, refinancing, supervisory, debt, insurance, planning and forecasting, analytical and guarantee tools. The advantages and disadvantages of these methods are revealed. The latter allowed to substantiate that to optimize the liquidity management process of a commercial bank should use their complex, its specific composition should be determined by the importance of a particular banking institution, its scale, ownership, customer service, existing counterparties, sources and areas of use, corporate governance in a banking institution.
Keywords: liquidity; liquidity management; methods of liquidity management; liquidity management tools; commercial bank